SUBSTRATE AND FERTILIZATION IN THE QUALITY OF Myrocarpus frondosus SEEDLINGS - Carpenedo Aimi, Suelen; Machado Araujo, Maristela; Fermino, Maria Helena; Almeri Tabaldi, Luciane; Claudino Zavistanovicz, Thairini; Mieth, Patrícia (Floresta, 2019)
Myrocarpus frondosus is a native species with high commercial timber value. Thus, the objective of this research was to evaluate the quality of seedlings of Myrocarpus frondosus in the nursery and to indicate the most adequate substrate and fertilization for the production of seedlings. The experiment was conducted in a completely randomized design, with four replications, in a factorial scheme, composed of four combinations of substrates: S1-100% commercial substrate (CS); S2 - 80% CS and 20% carbonated rice husk (CRH); S3 - 60% CS and 40% CRH; S4 - 40% CS and 60% CRH, and four fertilizations: NF – No fertilization; CRF – controlled release fertilizer (ammonium sulfate, simple superphosphate and potassium chloride); RRF – ready release fertilizer and micronutrients. Physical and chemical analyses were performed on the substrate. At 300 days after emergence, the following morphological variables were evaluated: (height, stem diameter, H/SD ratio, leaf area, root length, aerial dry mass, root dry mass, total dry mass, Dickson quality index) and the physiological variables chlorophyll a, chlorophyll b, carotenoids, initial fluorescence, maximum fluorescence, Fv/Fm ratio and electron transport rate). Regardless of the substrate and fertilization, slow growth of the species was observed, even for the best treatment, which was verified from the height (17.87 cm) and stem diameter (2.62 mm). The use of the commercial substrate (40%) with carbonated rice husk (60%) associated with the concentration of 6 g L-1 of controlled release fertilizer is recommended, since they present the best results for the morphological and physiological variables in the nursery in general.